Strategic Restructuring for Nonprofit Organizations: Mergers, Integrations, and AlliancesStrategic Restructuring for Nonprofit Organizations: Mergers, Integrations, and Alliances, by Kohm Amelia Piana David La. Westport, CT: Praeger, 2003. - Tsolmon, Urelmaa (Academy of Management Review, 2005)
The article reviews the book ?Strategic Restructuring for Nonprofit Organizations: Mergers, Integrations, and Alliances,? by Amelia Kohm and David La Piana.